(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Epilepsy, a neurological disorder characterized by abnormal brain electrical activity leading to recurrent seizures, affects approximately 1% of the Indian population, with higher prevalence in rural (1.9%) compared to urban (0.6%) settings. This interventional study conducted at a tertiary care hospital aimed to assess HRQOL among pediatric epilepsy patients using KINDL R questionnaires. Baseline data was collected from 110 pediatric patients, with two follow-up assessments conducted after interventions were implemented post the first follow-up. HRQOL was evaluated across three age groups: 3-6 years, 7-13 years, and 14-17 years. The study enrolled 110 patients and collected baseline data. Two follow-up assessments were conducted, and interventions were provided after the first follow-up. Following the intervention, HRQOL revealed positive changes in different age groups: 3-6 years (score changed from 17.37 + 2.31 to 20.79 + 4.10), 7-13 years (score changed from 53.29 + 3.96 to 58.88 + 5.68), and 14-17 years (score changed from 63.35 + 6.18 to 74.70 + 8.10). This study concludes that positive impact of pharmacist interventions on HRQOL among pediatric epilepsy patients. The findings underscore the effectiveness of pharmacist involvement in enhancing medication management and overall well-being. Further research could explore long-term effects and optimal strategies for improving HRQOL.